High prevalence of non‐alcoholic fatty liver disease among healthy male blood donors of urban India. Issue 2 (16th January 2019) - Duseja, Ajay; Najmy, Shaneez; Sachdev, Suchet; Pal, Arnab; Sharma, Rati Ram; Marwah, Neelam; Chawla, Yogesh
Abstract : Background: There is limited data on the community prevalence of non‐alcoholic fatty liver disease (NAFLD). The present study evaluated the prevalence of NAFLD in a large number of healthy male blood donors of urban north India. Methodology: In a prospective study performed over 18 months, voluntary blood donors fulfilling the requisite blood donation criteria and consenting to participate in the study were evaluated. The study received the approval of the institute's ethics committee. Diagnosis of NAFLD was made by excluding significant alcohol intake, ultrasound showing hepatic steatosis, and exclusion of transfusion associated infections. Subjects were also evaluated for various metabolic risk factors and the presence of metabolic syndrome. Results: Of 1388 subjects who consented for participation, 386 did not come for evaluation. Three females, nine (0.9%) HBsAg‐positive, and four (0.4%) anti‐HCV positive subjects were excluded. Of the 986 males evaluated with hepatobiliary ultrasound, 543(55.1%) had fatty liver on ultrasonography [15 (1.5%) alcoholic fatty liver and 528 (53.5%) NAFLD]. Among those with NAFLD, 469 (88.8%), 54 (10.2%), and 5 (0.9%) had mild, moderate, and severe hepatic steatosis, respectively. Subjects with NAFLD, when compared to those without NAFLD, had significantly higher age, BMI, waist circumference, blood pressure, total cholesterol and triglycerides, low‐density lipoprotein, and fasting plasma glucose. Multivariate regression analysis demonstrated age, BMI, waist circumference, systolic blood pressure, total cholesterol, and number of metabolic syndrome criteria as independent predictors of NAFLD. Conclusions: Urban Indian healthy male blood donors have a high prevalence of NAFLD. Abstract : Our study highlights a high prevalence of NAFLD in urban north Indian healthy male blood donors. Even though not evaluated in our study, many patients with fatty liver on ultrasound may have severe liver disease, that is, nonalcoholic steatohepatitis (NASH), NASH with significant fibrosis and even compensated NASH‐related cirrhosis, adding significantly to the present and future disease burden of chronic liver disease in Asia Pacific in general and in India in particular. A study to look into the environmental and genetic reasons would be required to check the spread of this lifestyle disease. The higher prevalence of NAFLD/hypertension and diabetes/IFG in healthy blood donors may represent the spread of a modern lifestyle epidemic in the general population and would require adequate preventive steps at various levels to check this menace.